PROKRASTINASI AKADEMIK PADA MAHASISWA - Musslifah, Anniez Rachmawati (Universitas Sahid Surakarta, 2014)
ABSTRACTProcrastination or procrastinate in doing and completing academic tasks is a common practice by most students, including working and completing thesis. Thesis is a task that must be completed by each student as a condition of graduation. Many fact ors cause students perform procrastination, ranging from delaying the start or finish a task, overdue tasks, and the gap between planned and actual performance.This study aims to look at the level of academic procrastination in students of psychology faculty Muhammadiyah University of Surakarta. The subject of research is a graduate student in the school term of more than 10 semesters or five years and have taken courses thesis over 2 semesters or 1 year.Results of this study that the level of procrastination in students of psychology faculty of the University of Muhammadiyah Surakarta moderate.Keywords: Academic Procrastination, thesis, students